Faktor Faktor Yang Mempengaruhi dan Strategi Peningkatan Pendapatan Usahatani Padi di Kecamatan Walenrang, Kabupaten Luwu - Ikram Ikram; Dewi Marwati Nuryanti; Naima Haruna (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2024)
Research on the pattern of development of empowerment of rice farmers towards income levels was carried out in Tombang Village, Walenrang District, Luwu Regency. This research was conducted from January to March 2024. The results of the study showed that rice farming in Walenrang District was profitable with variable costs of IDR 12,442,999 and fixed costs of IDR 407,471 so that the total costs incurred were IDR 12,850,470 and the production value was IDR 44,730,181 so that the net income received by farmers was IDR 31,879,711 per ha / planting season. Based on the t-test with regression analysis, the production factors that influence rice farming income in Walenrang District, namely Land area (X1), Labor costs (X2) and Capital (X3) have a significant effect on increasing production. Based on the F test on the regression analysis of production factors, the independent variables, namely land area (X1), labor costs (X2) and capital (X3), have a significant influence on increasing production in rice farming in Walenrang sub-district, Luwu district.